PRESCRIPTION COVERAGE IMPROVEMENT STRATEGY FOR PHARMACY OUTPATIENT INSTALLATION AT PREMIER JATINEGARA HOSPITAL - Susan Oktiwidya Ananda; Santi Novani (Universitas Islam Lamongan, 2024)
This study examines operational inefficiencies within the outpatient pharmacy at Premier Jatinegara Hospital, focusing on declining prescription coverage and its impact on patient care and hospital revenue. Using the DMAIC (Define, Measure, Analyze, Improve, Control) framework, the research systematically identifies key problem areas and proposes targeted improvement strategies. Internal analysis revealed issues such as frequent stockouts, inadequate real-time inventory management, workflow inefficiencies, and staffing shortages during peak hours. External analysis highlighted patient dissatisfaction due to long waiting times and supply chain disruptions caused by unreliable suppliers. To address these challenges, the study proposes a comprehensive improvement strategy focusing on upgrading the hospital’s data management system, implementing real-time inventory tracking, redesigning workflows, and enhancing staff training. The Plan-Do-Check-Act (PDCA) cycle forms the foundation of the implementation plan, ensuring the systematic execution and continuous monitoring of improvements. The recommended interventions aim to enhance patient safety, streamline inventory management, reduce waiting times, and improve overall service quality. Additionally, recommendations for future academic research include exploring the broader impact of technological integration on hospital efficiency and examining patient perceptions of pharmacy services. By addressing operational inefficiencies, this study provides valuable insights and practical solutions to enhance the efficiency and effectiveness of outpatient pharmacy services at Premier Jatinegara Hospital, ultimately supporting better patient outcomes and financial stability